Technical report: liquid overlay technique allows the generation of homogeneous osteosarcoma, glioblastoma, lung and prostate adenocarcinoma spheroids that can be used for drug cytotoxicity measurements - Jubelin, Camille; Muñoz-Garcia, Javier; Cochonneau, Denis; Ollivier, Emilie; Vallette, François; Heymann, Marie-Françoise; Oliver, Lisa; Heymann, Dominique (Frontiers in Bioengineering and Biotechnology, 2023)
The mechanisms involved in cancer initiation, progression, drug resistance, and disease recurrence are traditionally investigated through in vitro adherent monolayer (2D) cell models.However, solid malignant tumor growth is characterized by progression in three dimensions (3D), and an increasing amount of evidence suggests that 3D culture models, such as spheroids, are suitable for mimicking cancer development. The aim of this report was to reaffirm the relevance of simpler 3D culture methods to produce highly reproducible spheroids, especially in the context of drug cytotoxicity measurements. Human A549 lung adenocarcinoma, LnCaP prostate adenocarcinoma, MNNG/HOS osteosarcoma and U251 glioblastoma cell lines were grown into spheroids for 20 days using either Liquid Overlay Technique (LOT) or Hanging Drop (HD) in various culture plates. Their morphology was examined by microscopy.Sensitivity to doxorubicin was compared between MNNG/HOS cells grown in 2D and 3D. For all cell lines studied, the morphology of spheroids generated in round-bottom multiwell plates was more repeatable than that of those generated in flat-bottom multiwell plates. HD had no significant advantage over LOT when the spheroids were cultured in round-bottom plates.Finally, the IC50 of doxorubicin on MNNG/HOS cultured in 3D was 18.8 times higher than in 2D cultures (3D IC50 = 15.07 ± 0.3 µM; 2D IC50 = 0.8 ± 0.4 µM; *p<0.05). In conclusion, we propose that the LOT method, despite and because of its simplicity, is a relevant 3D model for drug response measurements that could be scaled up for high throughput screening.